How do we adapt hospital care in patients with hyperglycemia and COVID-19? - Luis Grosembacher (Revista de la Sociedad Argentina de Diabetes, 2021)
The COVID-19 pandemic that is going through the entire world caused a situation of global crisis in all health systems. This crisis forced us to make emergent changes to achieve adequate inpatient care in critical and non-critical areas. Therefore, the health personnel (HCP) faced new challenges, and resorted to tools for outpatient use (such as continuous glucose monitoring and telemedicine, which facilitated communication spaces between the HCP with the hospitalized patient), and also used the technology for the transmission of diagnoses and treatments for patients at a distance.